CONSTRUCTION WORKERS' SUBJECTIVE AND OBJECTIVE FATIGUE MEASUREMENT ON MULTISTOREY PROJECT - Anthony Jiram, Wilson Rangga; Ismail, Azizah Binti; Tamjehi, Sitti Diana (Journal of Sustainable Technology and Applied Science (JSTAS), 2022)
Quality, cost, and time are the primary targets of construction projects; the working environment, occupational safety, and health are also crucial. An employer can implement occupational safety and health (OHS) by providing rules and appeals to minimise workplace accidents. Several studies found that workers' stress and fatigue caused workplace accidents. Therefore, this study aimed to investigate workers' fatigue based on subjective and objective measurements using surveys; the researchers distributed questionnaires and measured the pulse of 84 workers in multi-storey building construction projects. The subjective analysis revealed that workers' fatigue reached a total score of 77.81, categorised in level 3 and classified as high fatigue. Meanwhile, the objective analysis proves that workers' pulse rate indicates heavy load work and high fatigue levels. There is a positive but not significant correlation between subjective and objective variables from the Pearson correlation test. Thus, the study concluded that corrective action in implementing occupational health and safety was imperative. In addition, employers need to use work methods to minimise workers' fatigue in construction projects. Investigating fatigue is expected to prevent work accidents in constructing multi-storey buildings.